Influence de la composition chimique du sol sur la teneur en éléments nutritifs et le rendement du manioc (Manihot esculenta Crantz, Euphorbiaceae) dans deux zones agro-écologiques du Cameroun - Temegne, N.C.; Ajebesone, F.N.; Kuate, A.F. (African Journals Online, 2015)
A study was conducted to evaluate the effect of soil chemical composition on nutrient uptake and yield of cassava in two agro-ecological zones of Cameroon. Soil and plant samples were obtained from twelve month old pure culture cassava fields at Ekona (zone 4) and Ongot village (zone 5). An improved variety (8034) and two local varieties (Local Red at Ekona and Bassa Noire at Ongot) were used. Results showed that the soil from Ekona (Andosol) was significantly higher in nutrients (total nitrogen: 1.34%; phosphorus available: 15 mg.kg-1) than the soil from Ongot [(Ferralsols), (total nitrogen: 0.11%; phosphorus available: 4 mg.kg-1)]. The improved variety accumulated significantly more total fresh biomass and root yield than the local varieties, irrespective of the site. Similarly, nutrient uptake was higher with the improved variety across the zones. A positive and highly significant correlation (r2 :0.999, p<0.001) was observed between nutrient uptake by cassava and soil nutrient availability. Thus, it may be concluded that the quantity of nutrient in the leaves and roots of cassava is proportionate to the quantity of nutrient elements in the soil. This preliminary result constitutes a solid base for the determination of an appropriate fertilizer scheme for cassava cultivation in Cameroon.